2019
DOI: 10.3390/ijerph17010094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Self-Concept, Emotional Isolation, and Family Functioning on Attitudes towards Physical Education in Adolescents: Structural Equation Analysis

Abstract: 1) Background: The present research seeks to define and contrast an explanatory model of physical self-concept, emotional isolation, attitude towards physical education, and family functioning, and analyse the existing associations between these variables.(2) Methods: The sample was made up of 2388 adolescents (43.39% male and 56.61% female), with ages of 11-17 years (M = 13.85; SD = 1.26) from Spain. Self-concept (AF-5), Isolation (UCLA), Attitude towards Physical Education (CAEF), and Family Functioning (APG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…The findings suggested that general physical self-concept and its sub-domains (i.e., perceived competence, perceived fitness and perceived appearance) are significantly associated with physical activity in young people. The research conducted by Padial-Ruz et al [18] found that self-concept, in all of its dimensions, achieved a higher level among individuals who engaged in PA. This confirms the positive effects of PA at a physical and mental level, on social relations, this being even more evident during the adolescent stage [20].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The findings suggested that general physical self-concept and its sub-domains (i.e., perceived competence, perceived fitness and perceived appearance) are significantly associated with physical activity in young people. The research conducted by Padial-Ruz et al [18] found that self-concept, in all of its dimensions, achieved a higher level among individuals who engaged in PA. This confirms the positive effects of PA at a physical and mental level, on social relations, this being even more evident during the adolescent stage [20].…”
Section: Discussionmentioning
confidence: 97%
“…Research studies demonstrate that adolescents, both males and females, who participate regularly in physical activity reported a more positive physical self-concept than those who were not active [17]. The study by Padial-Ruz et al [18] showed that self-concept was shown by individuals with higher levels of physical activity. This confirms the positive effects of physical activity at a physical and mental level and on relatedness [19], and it is more evident during the adolescent stage [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, self-concept is especially important in adolescence, since everyday emotions and feelings are essential in personal development, which is subjective and changes according to external factors and new contexts of life [19]. As a matter of fact, self-concept represents a protective factor against disruptive behaviour, enhancing both mental health and positive peer relationships [20]. Consequently, the psychological construction of a positive self-concept in students during the school years produces successful socio-emotional situations and educational settings [21].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that behavioral levels of activities performed during adolescence may follow into adulthood [10,24,35,47,48,49,50]. Although the effects of chronic noncommunicable diseases manifest in adulthood, their development begins in childhood and adolescence [29].…”
Section: Resultsmentioning
confidence: 99%